Implementation of Islamic Sharia in Aceh (Study on the Dynamics of Legalization and Permits for the Implementation of Islamic Sharia in Aceh Province) - Mustafa Kamal; Muntasir Muntasir; Marzuki Marzuki (Budapest International Research and Critics University, 2021)
This research examineswhat is the history of the process and dynamics of the local government's policy regarding permits for the implementation of Islamic law in Aceh. This research is qualitative descriptive research with content analysis approach. The steps taken in the research include data collection and data analysis. First, the data is taken from the source such as the book entitled Islamic Shari'a in Aceh (Problematics of Sharia Implementation). The results showed that: The Birth of the Legalization of Islamic Sharia in Aceh occurred in 1999 after going through a long struggle against various policies and conflicts (movements needed by Acehnese community leaders). Among them is the policy of the Central Government as a result of the Round Table Conference (KMB) which has implications for the dissolution of the Aceh Province which has an effect on the existence of the Syar'iyah Court, which was previously an apparatus of the Aceh Province. This was further exacerbated by the issuance of Law No. 1 of 1950 which contained the dissolution of all autonomous courts and merged them into state courts. The dynamics of permits for the implementation of Islamic Shari'ah in Aceh are vulnerable to those responsible for implementing Islamic Shari'ah (Pemda and related institutions) in making policies on the implementation of Islamic Shari'ah. This was caused by two things, namely: First, there were certain parties who were worried and accused that the implementation of Islamic Shari'ah in Aceh would reduce and not be in line with the protection of human rights and women. The two permits have given rise to formidable challenges, because it can be said that this is a new era in the study and development of fiqh, especially in Aceh.